A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae) - Galileo, Maria Helena M.; Santos-Silva, Antonio; Heffern, Daniel (Zootaxa, 2017)
Hippopsis raberi sp. nov. is described from Darién National Park, Panama. A key to 40 species of the genus is provided.